The effects of mechanical force on fibroblast behavior in cutaneous injury - Berry, Charlotte E.; Downer, Mauricio; Morgan, Annah G.; Griffin, Michelle; Liang, Norah E.; Kameni, Lionel; Laufey Parker, Jennifer B.; Guo, Jason; Longaker, Michael T.; Wan, Derrick C. (Frontiers in Surgery, 2023)
Wound healing results in the formation of scar tissue which can be associated with functional impairment, psychological stress, and significant socioeconomic cost which exceeds 20 billion dollars annually in the United States alone. Pathologic scarring is often associated with exaggerated action of fibroblasts and subsequent excessive accumulation of extracellular matrix proteins which results in fibrotic thickening of the dermis. In skin wounds, fibroblasts transition to myofibroblasts which contract the wound and contribute to remodeling of the extracellular matrix. Mechanical stress on wounds has long been clinically observed to result in increased pathologic scar formation, and studies over the past decade have begun to uncover the cellular mechanisms that underly this phenomenon. In this article, we will review the investigations which have identified proteins involved in mechano-sensing, such as focal adhesion kinase, as well as other important pathway components that relay the transcriptional effects of mechanical forces, such as RhoA/ROCK, the hippo pathway, YAP/TAZ, and Piezo1. Additionally, we will discuss findings in animal models which show the inhibition of these pathways to promote wound healing, reduce contracture, mitigate scar formation, and restore normal extracellular matrix architecture. Recent advances in single cell RNA sequencing and spatial transcriptomics and the resulting ability to further characterize mechanoresponsive fibroblast subpopulations and the genes that define them will be summarized. Given the importance of mechanical signaling in scar formation, several clinical treatments focused on reducing tension on the wound have been developed and are described here. Finally, we will look toward future research which may reveal novel cellular pathways and deepen our understanding of the pathogenesis of pathologic scarring. The past decade of scientific inquiry has drawn many lines connecting these cellular mechanisms that may lead to a map for the development of transitional treatments for patients on the path to scarless healing.